A mesoporous polysulfonic acid-formaldehyde polymeric catalyst for biodiesel production from Jatropha curcas oil. (August 2021) - Laskar, Ikbal Bahar; Changmai, Bishwajit; Gupta, Rajat; Shi, Da; Jenkinson, Kellie J.; Wheatley, Andrew E.H.; Rokhum, Lalthazuala
Abstract: A highly reactive acid-functionalized polymer is prepared by the simple condensation of aqueous formaldehyde and p -phenolsulfonic acid and used as a solid catalyst in concerted (trans)esterification. This yields biodiesel from Jatropha oil without the need to remove water by-product from the reaction mixture. An isolated biodiesel yield of 98 ± 2% is achieved using a catalyst loading of 10 wt %, methanol:oil ratio of 12:1, temperature of 90 °C, and reaction time of 6 h. The high activity of our catalyst is attributed to its porous nature and the co-inclusion of reactive SO3 H sites and phenolic OH groups. Advantageously, these groups are hydrophilic, allowing the catalyst to remain highly active in the presence of H2 O. Nine methyl ester components are identified in the biodiesel product, with 9-octadecanoic acid methyl ester (C18:2, 64.92%) and hexadecanoic acid methyl ester (C16:0, 16.44%) as the major constituents. The catalyst is evaluated over 4 cycles, maintaining a 92 ± 2% isolated yield. Physicochemical analysis of the spent catalyst by SEM-EDX suggests this decrease is due to some loss of mesoporosity and sulfur content. Graphical abstract: Image 1